Analysis of the productivity value of hebel couple's work using work study method in building construction project pilot scale product development facility - Kresnadi Widyanto Kusuma; Abdul Rochman (Institute of Computer Science (IOCS), 2023)
Construction is a field in the world of property in the part of planning and construction involving architects and civil engineering. Project is a complex activity and has a nature that cannot occur repeatedly, has a limited time using certain resources with the aim of producing a product. One aspect of a successful construction project is resources. This study uses the work study method, namely taking direct observation data in the field by comparing the work group that has been created with the 2008 SNI rules for working on 1 m2 of hebel installation work. The result of this study is that the group that has the highest productivity value is work group 3 because the average volume produced is large compared to other groups. The most efficient working group is group 2 because with not too high costs it can produce an average volume of 15.6875 m2 per day. The total wage paid for hebel wall installation work per 1 m2 of work group 1 amounted to Rp 126,329.00. Group 3 (productive) amounted to Rp 183,166.00. Wages for work group 2 (efficient) amounted to Rp 166,467.00. Working group 2 is the most optimal working group. The volume of work that can be produced by the working group is 15.6875 m2 hebel pairs in 1 working day.